2013 AAFP Feline Vaccination Advisory Panel Report. Issue 9 (September 2013) - Scherk, Margie A; Ford, Richard B; Gaskell, Rosalind M; Hartmann, Katrin; Hurley, Kate F; Lappin, Michael R; Levy, Julie K; Little, Susan E; Nordone, Shila K; Sparkes, Andrew H
Rationale: This Report was developed by the Feline Vaccination Advisory Panel of the American Association of Feline Practitioners (AAFP) to provide practical recommendations to help clinicians select appropriate vaccination schedules for their feline patients based on risk assessment. The recommendations rely on published data as much as possible, as well as consensus of a multidisciplinary panel of experts in immunology, infectious disease, internal medicine and clinical practice.